MANAJEMEN UJIAN PENTAS DI SANGGAR LESTARI WIDODO WIRYOTOMO TULUNGAGUNG - Saputra, Faizul Ilmi; Senyum Sadhana; Welly Suryandoko; Anbie Haldini Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A stage examination is more than a tool to measure learners' achievement in nonformal dance education it also demands systematic management to run well. This study describes the role of George R. Terry's management functions planning, organizing, actuating, and controlling (POAC) in the successful organization of stage examinations at Sanggar Tari Lestari Widodo Wiryotomo (LWW), Tulungagung. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, then analyzed with Miles and Huberman's interactive model. Findings show that planning is reflected in scheduling, selecting dance material by class level, and preparing technical and administrative assessment needs. Organizing takes shape through a committee structure with clearly divided tasks per section. Actuating is evident in the examination running on schedule, supported by fairly solid coordination among committee members. Controlling is carried out through evaluating both the process and the assessment outcomes, serving as a basis for future improvement. One key finding: the jury's scoring form still lacks a standardized written rubric, leaving room for subjectivity. Overall, these four management functions play a significant role in the success of the stage examination at Sanggar LWW.